A Ditopic Phosphane‐decorated Benzenedithiol as Scaffold for Di‐ and Trinuclear Complexes of Group‐10 Metals and Gold. Issue 13 (20th February 2020) - Schlindwein, Simon H.; Sibold, Carlo; Schenk, Mareike; Ringenberg, Mark R.; Feil, Christoph M.; Nieger, Martin; Gudat, Dietrich
Abstract : The ability of 3‐(diphenylphosphinomethyl)‐benzene‐1, 2‐dithiol (pbdtH2 ) to act as ditopic ligand was probed in reactions with selected group‐10‐metal complexes. Reactions with [(cod)PdCl2 ] afforded a mixture of products identified as [Pd(pbdtH)2 ], [Pd2 (μ2 ‐pbdt)2 ] and [Pd3 (μ2 ‐pbdt)2 Cl2 ]. The polynuclear complexes could be isolated after suitably adjusting the reaction conditions, and heating of a mixture in a microwave reactor effected partial conversion into a further complex [Pd3 (μ2 ‐pbdt)3 ]. Reaction of pbdtH2 with [Ni(H2 O)6 Cl2 ] gave rise to a complex [Ni2 (μ2 ‐pbdt)2 ], which was shown to undergo two reversible 1e – ‐reduction steps. Reaction of [Pd(pbdtH)2 ] with [Au(PPh3 )Cl] afforded heterotrinuclear [PdAu2 (μ2 ‐pbdt)2 (PPh3 )]. All complexes were characterized by analytical, spectroscopic and single‐crystal X‐ray diffraction studies. Their molecular structures confirm the ability of the pbdt 2– unit to support simultaneous P, S‐ and S, S‐chelating coordination to two metal centers. Abstract :